The influence of teacher's attitudes and beliefs into technology-related skills, at Unidad Educativa Tumbaco during the 2010-2011 school year - Collaguazo Carrera, Héctor Gonzalo (2016)
This paper was performed at Educational Unit Tumbaco where teachers do not have enough skills in the use of new Technology, also tries to identify the causes about teacher's lack of knowledge and training in the use of new technology and its application. Hence, the purpose of this research consisted in finding out factors such as teachers' attitudes and beliefs related to the use of new technology in teaching. Another purpose was to study how to improve the skills using new technology, and its relation between teachers' attitudes towards new technology. This work focused on the development of skills in the use of new technology and explore if teachers' beliefs affected into technology-related skills. It was applied the descriptive and inferential statistics method to analyze and develop a more detailed investigation with the use of surveys to teachers and students; Who were the key players that helped detect this problem, who selflessly gave their collaboration once was explained the technique used.